Menstrual blood‐derived mesenchymal stem cells attenuate inflammation and improve the mortality of acute liver failure combining with A2AR agonist in mice. Issue 9 (5th April 2021) - Chen, Dazhi; Zeng, Ruichao; Teng, Guigen; Cai, Chao; Pan, Tongtong; Tu, Hanxiao; Lin, Hongwei; Du, Qingjing; Wang, Huahong; Chen, Yongping
Abstract: Background and Aim: Acute liver failure (ALF) poses a serious public health issue. The menstrual blood‐derived mesenchymal stem cells (MenSCs) have been applied to cure various liver‐related diseases. However, the efficacy and mechanism are far from clear. This study aims to explore the efficacy and potential mechanism of MenSCs to cure ALF. Methods: We investigate the potential mechanism of MenSCs on the ALF in vitro and in vivo . A2A adenosine receptor (A2AR) activation was investigated as the potential reinforcer for MenSCs treatment. Lipid polysaccharide/d ‐galactosamine (d ‐GalN) was employed to induce ALF. Diverse techniques were used to measure the inflammatory cytokines and key signaling molecules. Hematoxylin–eosin stain and aminotransaminases were applied to evaluate the liver injury. Flow cytometry was employed to assess the T cells. Results: The MenSCs can decrease the lipid polysaccharide‐induced inflammatory cytokine elevation and related signaling molecules in ALF, including TLR4, phosphorylated‐NF‐kBp65 (p‐NF‐kBp65), PI3K, and p‐AKT, p‐mTOR and p‐IKK in vitro . Moreover, MenSCs also can significantly reverse the liver injury, inflammatory cytokines elevation and related signaling molecules increase, and Treg/Th17 ratio decrease in vivo . In addition, MenSCs plus A2AR agonist can enhance the above changes. Conclusions: The MenSCs can attenuate the ALF‐induced liver injury via inhibition of TLR4‐mediated PI3K/Akt/mTOR/IKK signaling. Then, this inhibits the p‐NF‐κBp65 translocate into nuclear, which causes a decrease of inflammatory cytokines release. Moreover, A2AR agonist can play a synergic role with MenSCs and enhance the above‐mentioned effects.